2015
DOI: 10.1088/2040-8978/18/1/014007
|View full text |Cite
|
Sign up to set email alerts
|

Squeezed light and correlated photons from dissipatively coupled optomechanical systems

Abstract: We study theoretically the squeezing spectrum and second-order correlation function of the output light for an optomechanical system in which a mechanical oscillator modulates the cavity linewidth (dissipative coupling). We find strong squeezing coinciding with the normal-mode frequencies of the linearized system. In contrast to dispersive coupling, squeezing is possible in the resolved-sideband limit simultaneously with sideband cooling. The second-order correlation function shows damped oscillations, whose p… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 23 publications
1
17
0
Order By: Relevance
“…This implies that, for the dissipative coupling system, this regime is extremely unfavorable for the squeezing purposes. Our results also provide qualitative explanation for the numerical results on the optomechanical instability obtained by Nunnenkamp and coworkers 4,5,7 . Specifically, we have demonstrated that, for small detuning, the stability diagrams for the cases of purely dispersive and purely dissipative coupling are complimentary.…”
Section: Discussionsupporting
confidence: 83%
“…This implies that, for the dissipative coupling system, this regime is extremely unfavorable for the squeezing purposes. Our results also provide qualitative explanation for the numerical results on the optomechanical instability obtained by Nunnenkamp and coworkers 4,5,7 . Specifically, we have demonstrated that, for small detuning, the stability diagrams for the cases of purely dispersive and purely dissipative coupling are complimentary.…”
Section: Discussionsupporting
confidence: 83%
“…Currently, with the rapid progress of practical technologies in cavity optomechanics, the mechanical resonator can be cooled down close to the quantum ground state [2][3][4]. Thus it is possible to explore quantum effects in macroscopic systems, including superposition state [5,6], entanglement [7][8][9], squeezing of light [10][11][12][13][14][15][16], squeezing of the mechanical resonator , etc.…”
Section: Introductionmentioning
confidence: 99%
“…The dissipative coupling can do virtually all the jobs of the dispersive coupling, such as optomechanical cooling, optical squeezing, and mechanical sensing while the physical conditions and mechanisms encountered in it are rather different. Among theoretical predictions analyzed for dissipative-coupling-assisted systems are the possibility of simultaneous squeezing and sideband cooling 6 , a stable optical-spring effect, which is notfeed-back-assisted 8 , a virtually perfect squeezing of the optical noise in a system exhibiting no optomechanical instability 13 , and not-feed-back-assisted cooling of a mechanical oscillator under the resonance excitation 10 , the latter also demonstrated experimentally 23 .…”
Section: Introductionmentioning
confidence: 98%
“…To fill the gap, those authors have introduced the so-called dissipative coupling, which originates from the dependence of the cavity decay rate on the position of the mechanical oscillator. Since then such a coupling has been attracting an appreciable attention of theorists [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] and experimentalists [22][23][24][25][26][27] . The dissipative coupling can do virtually all the jobs of the dispersive coupling, such as optomechanical cooling, optical squeezing, and mechanical sensing while the physical conditions and mechanisms encountered in it are rather different.…”
Section: Introductionmentioning
confidence: 99%